Systemic Inflammation and Oxidative Stress in Childhood Obesity: Sex Differences in Adiposity Indices and Cardiovascular Risk - Tjaša Hertiš Petek; Evgenija Homšak; Mateja Svetej; Nataša Marčun Varda (Biomedicines)
Background: Systemic inflammation and oxidative stress are fundamental contributors to the onset of conditions related to childhood obesity, such as cardiovascular (CV) diseases. We aimed to assess CV risk in childhood obesity by examining sex differences in adiposity indices, cardiometabolic profiles, inflammation, and oxidative stress biomarkers. We also aimed to assess the potential of the interferon-inducible T-cell alpha chemoattractant (I-TAC/CXCL11) as a novel biomarker. Methods: Eighty children (36 girls) aged 5–18 years with overweight, obesity, or normal weight were analyzed. Fasting blood samples were obtained to assess C-reactive protein (CRP), leukocytes, myeloperoxidase (MPO), adiponectin, monocyte chemoattractant protein-1, superoxide dismutase-1, I-TAC/CXCL11, and a comprehensive cardiometabolic profile, including glucose, lipid, renal, liver, and thyroid function markers. Adiposity indices were determined using bioelectrical impedance analysis (BIA) and anthropometric measures, including BMI, waist-to-hip and waist-to-height ratios, and visceral and subcutaneous fat thickness. Blood pressure (BP) and pulse wave velocity were also evaluated. Results: Girls had less central obesity and fewer CV risk factors than boys, despite having similar total fat mass. Both girls and boys with overweight or obesity showed higher CRP levels. Girls with excess weight had increased leukocyte counts, while boys had elevated MPO levels, which correlated positively with adiposity indices, systolic BP, and homocysteine, and negatively with HDL. I-TAC/CXCL11 levels were similar across groups. Conclusions: Adiposity indices are essential for evaluating CV risk in children and adolescents, with sex differences underscoring the need for tailored approaches. MPO correlated significantly with CV risk markers, supporting its inclusion in routine assessments. I-TAC/CXCL11 warrants further study in childhood obesity.